(untitled) (Journal of Universal Science Research, 2025)
This article examines the role and importance of management in education, the need for a deep analysis of the internal and external environment of an educational institution, identifying existing opportunities, solving existing problems and developing new strategies, as well as ensuring effective management in accordance with the goals and objectives of educational institutions.